2004
DOI: 10.1002/ejic.200400167
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Thermotropic and Lyotropic Liquid Crystals of Bis(N‐alkylethylenediamine)silver(I) Nitrate

Abstract: We have synthesized bis(N-hexylethylenediamine)silver(I) nitrate ([Ag(hex-en)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The preparation of silver(I) alkylethylenediamine nitrates was followed by the previous procedures [20,31,45]. The counter-ion exchange was performed by mixing the silver nitrate complexes (0.01 mol, 4.6 g or 5.1 g) and KTFSA (0.01 mol, 3.5 g, supplied from Morita Chemicals) in methanol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation of silver(I) alkylethylenediamine nitrates was followed by the previous procedures [20,31,45]. The counter-ion exchange was performed by mixing the silver nitrate complexes (0.01 mol, 4.6 g or 5.1 g) and KTFSA (0.01 mol, 3.5 g, supplied from Morita Chemicals) in methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Our X-ray crystallographic analysis of bis(N-dodecylethylenediamine) silver(I) nitrate revealed that this complex has a dinuclear structure in the crystalline state, whereas in methanol the dinuclear structure dissociated appreciably into a mononuclear complex [31]. In the present systems with shorter alkyl chains, even if the alkylethylenediamine silver(I) complex has a dinuclear structure in the crystalline state, it is presumed that the Ag-IL complex will become mononuclear in the liquid state rather than dinuclear for the following reasons: (1) AILs generally have polarities similar to ethanol [43,44], so the Ag-IL itself can be regarded as a solvent with polarity similar to ethanol.…”
Section: Solubilities Of the Ag-ils And Pilsmentioning
confidence: 97%
See 1 more Smart Citation
“…19 However, the difference in the number of ligands is distinctly reflected in the Stokes radii, which are generally smaller than those estimated from the molecular model in organic solvents for metal complex surfactants. 12, 20 The concentration dependence of the diffusion coefficients shows a small but clear downward deviation from the linearity at 0.4 mol kg −1 for La(oct-ala) 3 ; the decrease can thus be attributed to an increase in the size by the aggregation of the solutes. The break point indicates the gradual start of the aggregation.…”
Section: Self-assemblies Of the Metal Complexes In Solutions Studied ...mentioning
confidence: 95%
“…(Manna et al, 2001;Iida et al, 2004) These surfactants are structurally similar to gemini-type surfactants which have been extensively studied and showed a variety of aggregation phenomena due to multi-alkyl chains and bulky headgroup. (Zana & Xia, 2003) As the metallosurfactants have additional properties due to containing transition metals, multi-chained metallosurfactants are oriented to a wide range of potential applications such as metallomesogens, optoelectronic devices, magnetic resonance imaging, homogeneous catalysis, and nanoparticles.…”
Section: Silver(i)-alkylethylenediamine Ils and Alkylethylenediaminiumentioning
confidence: 99%